Norma Kebugaran Fisik untuk Calon Wasit Pencak Silat Tingkat Daerah: Pendekatan Tes Baterai di Kota Serang - Prama Dhani, Danang; Triprayogo, Rian; Irsyad, Naufallathuf Yaquttul; Fathannisa, Tulliss Bial; Bayu Utomo, Andy Widhiya (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2026)
The assessment of pencak silat referee competence has long been dominated by technical and theoretical evaluations, yet it lacks standardized objective physical fitness parameters, particularly for the novice category. This study aims to develop physical condition battery test norms as a biological evaluation instrument for prospective regional-level referees in Serang City in 2026. Employing a quantitative descriptive design, the study involved 21 novice referees selected via total sampling. Data were collected through five measurement dimensions: Multistage Fitness Test (MFT), Whole Body Reaction (WBR), Balance, Push Up, and Vertical Jump. The conversion procedure involved aggregating raw scores from all instruments, which were subsequently classified using a 5-point scale Norm-Referenced Assessment (PAN) based on the Mean (22.9) and Standard Deviation (7.8). The results established five physical readiness categories: Excellent (Score ≥ 35), Good (27-34), Average (19-26), Poor (12-18), and Very Poor (≤ 11). These findings provide an evidence-based selection framework that enables the IPSI Serang City Branch to validate the physical readiness of referees objectively prior to official championship assignments.